Does multivessel revascularization fit all patients with STEMI and multivessel coronary artery disease? A systematic review and meta-analysis. (August 2021) - Hu, Meng-Jin; Li, Xiao-Song; Jin, Chen; Yang, Yue-Jin
Abstract: Objective: We sought to assess the relative merits of different revascularization strategies in patients with ST-segment elevation myocardial infarction (STEMI) and multivessel coronary artery disease complicated by cardiogenic shock or chronic total occlusion (CTO). Background: Recent randomized trials and meta -analysis have suggested that multivessel percutaneous coronary intervention (PCI) is associated with better outcomes in patients with STEMI and multivessel coronary artery disease, however, patients complicated by cardiogenic shock or CTO were excluded. Methods: Studies that compared multivessel PCI (immediate or staged) with culprit-only PCI in patients with STEMI and multivessel coronary artery disease complicated by cardiogenic shock or CTO were included. Random odd ratio (OR) and 95% confidence interval (CI) were conducted. Results: Sixteen studies with 8695 patients complicated by cardiogenic shock and eight studies with 2259 patients complicated by CTO were included. In patients complicated by cardiogenic shock, a strategy of CO-PCI was associated with lower risk for short-term renal failure (OR: 0.75; 95% CI: 0.61–0.93; I 2  = 0.0%), with no significant difference in MACE, all-cause mortality, re-infarction, revascularization, cardiac death, heart failure, major bleeding, or stroke compared with an immediate MV-PCI strategy. In patients complicated by CTO, a strategy of CO-PCI was associated with higher risk for long-term MACE (OR: 2.06; 95% CI: 1.39–3.06; I 2  = 54.0%), all-cause mortality (OR: 2.89; 95% CI: 2.09–4.00; I 2  = 0.0%), cardiac death (OR: 3.12; 95% CI: 2.05–4.75; I 2  = 16.8%), heart failure (OR: 1.99; 95% CI: 1.22–3.24; I 2  = 0.0%), and stroke (OR: 2.80; 95% CI: 1.04–7.53; I 2  = 0.0%) compared with a staged MV-PCI strategy, without any difference in re-infarction, revascularization, or major bleeding. Conclusions: For patients with STEMI and multivessel coronary artery disease complicated by cardiogenic shock, an immediate multivessel PCI was not advocated due to a higher risk for short-term renal failure, whereas for patients complicated by CTO, a staged multivessel PCI was advocated due to reduced risks for long-term MACE, all-cause mortality, cardiac death, heart failure, and stroke.